2019
DOI: 10.1186/s13014-019-1255-7
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric evaluation of four whole brain radiation therapy approaches with hippocampus and inner ear avoidance and simultaneous integrated boost for limited brain metastases

Abstract: AimsTo perform a dosimetric evaluation of four different simultaneous integrated boost whole brain radiotherapy modalities with hippocampus and inner ear avoidance in the treatment of limited brain metastases.MethodsComputed tomography/magnetic resonance imaging data of 10 patients with limited (1–5) brain metastases were used to replan step-and-shoot intensity-modulated radiotherapy (sIMRT), dynamic intensity-modulated radiation therapy (dIMRT), volumetric-modulated arc therapy (VMAT), and helical tomotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 33 publications
4
22
0
Order By: Relevance
“…For hippocampal sparing in WBRT, slightly superior homogeneity indices and target coverage were found for tomotherapy when compared to IMRT and VMAT [31,32]. However, the availability of tomotherapy is limited, and the treatment planning time is significantly longer.…”
Section: Discussionmentioning
confidence: 99%
“…For hippocampal sparing in WBRT, slightly superior homogeneity indices and target coverage were found for tomotherapy when compared to IMRT and VMAT [31,32]. However, the availability of tomotherapy is limited, and the treatment planning time is significantly longer.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, in the comparison of two modalities (VMAT and helical tomotherapy), it is seen that the average of minimum, mean and maximum doses received by both right and left hippocampal regions are lower in helical tomotherapy treatment planning system (TPS). Also, they concluded that the inner ear dose was reduced to Dmean ≤15Gy in all four planning modalities (27) .…”
Section: Discussionmentioning
confidence: 98%
“…In their study, Jiang et al showed that 4 planning modalities (sIMRT, dIMRT, VMAT and Tomo) satisfied the RTOG 0933 protocol dose compatibility criteria for hippocampal sparing. Using the planning modalities reported above with an acceptable mean PTV brain coverage (88.2%-92.6), delivery of similar mean doses to the hippocampi were accomplished (27) . In our study, in the comparison of two modalities (VMAT and helical tomotherapy), it is seen that the average of minimum, mean and maximum doses received by both right and left hippocampal regions are lower in helical tomotherapy treatment planning system (TPS).…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the risk of cognitive decline and improve clinical outcomes, attempts have been made at adding simultaneous integrated boost (SIB) to HS-WBRT. For example, Jiang et al have demonstrated that HS-WBRT with SIB can be implemented using four modern RT techniques, including step-and-shoot IMRT, dynamic IMRT, VMAT, and helical tomotherapy [26]. Specifically, they prescribed 45-50 Gy to metastatic lesion, and 30 Gy to the whole brain, in 10 fractions.…”
Section: Plos Onementioning
confidence: 99%